The effectiveness of the ethnomathematics-integrated Problem-Based Learning (PBL) model on students’ mathematical abilities: A meta-analysis study - Maulida; Noor Fajriah; Taufiq Hidayanto (Journal Focus Action of Research Mathematic (Factor M), 2025)
Numerous primary studies have explored the impact of the Problem-Based Learning (PBL) model incorporating ethnomathematics on students’ mathematical abilities. However, variations in research findings have hindered the formation of a consistent conclusion. This study aimed to evaluate the overall effect of the PBL model based on ethnomathematics on students’ mathematical competencies through a systematic review and meta-analysis. Eleven relevant articles were selected via Google Scholar using the Publish or Perish tool and screened based on PRISMA guidelines, including identification, screening, eligibility, and inclusion phases. Data analysis was conducted using Comprehensive Meta-Analysis (CMA) software version 3.0. The calculated effect size, based on Hedges' g and employing a random-effects model, was 0.974, which is categorised as large. Further analysis examined two moderating variables: types of mathematical abilities and educational level. The results demonstrate that the PBL model grounded in ethnomathematics significantly enhances mathematical abilities, particularly in problem-solving and critical thinking skills. Additionally, the model is notably effective at the elementary and junior high school levels. These findings underscore the value of integrating local cultural contexts into mathematics instruction and support the development of innovative, culturally responsive learning strategies that align with modern educational goals.